Prospective, randomized, open label comparative study of efficacy of atorvastatin versus atorvastatin with vitamin D3 in patients with dyslipidemia attending tertiary care hospital - Rani, Motakatla Usha; Karuppiah, Chitra; Kiruthiga, Novaladi; Rayavarapu, Vivek (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Cardiovascular diseases are one of the most important group of diseases causing premature mortality and morbidity. Dyslipidemia is an independent risk factor for cardiovascular diseases and is a disorder of lipoprotein metabolism. Various research studies support role of vitamin D against dyslipidemia. Vitamin D concentration positively correlates with HDL cholesterol and negatively with serum LDL and triglyceride levels. Vitamin D supplementation to Atorvastatin appeared to have increased cholesterol lowering activity more than either substance did alone. Methods: The study was conducted in an outpatient department of general medicine for a duration of 12 weeks in a tertiary care hospital. Total of 100 patients with dyslipidemia were selected based on measurement of lipid profile. Out of 100 patients, 50 patients under group A were treated with atorvastatin 10mg and balance 50 patients under group B treated with atorvastatin and Vitamin D3 1000 IU/day orally. Patients were followed up monthly for 3 months and lipid profile was assessed at baseline and at the end of study. The baseline characteristics were similar in both study groups. Results: On comparing groups at the end of 12 weeks mean LDL, triglycerides and VLDL were significantly reduced in group B than group A with p<0.001. The mean HDL level too increased in group B than group A with p<0.001. Conclusions: Fasting plasma lipid profile improvement was higher in the atorvastatin with vitamin D3 group compared to atorvastatin group.